Sistem Informasi Data Jadwal Penyiaran Berbasis Web - Muhammad Ghaffar Shidqi, Mutammimul Ula (Jurnal Elektronika dan Teknologi Informasi, 2023)
The development of information and communication technology, which is increasingly evident in this modern era, helps human work to be more efficient and effective in any field. At present, at RRI Lhokseumawe the broadcast schedule data collection system used is a manual system in the form of radio broadcast schedule data collection using Microsoft Word by broadcasting division officers. The system design methodology is based on a manual system that is still valid, in which an officer inputs broadcast schedule data that runs on that day and can then be printed and then managed again by theofficer. This research resulted in a web-based broadcast schedule data application system so that RRI Lhokseumawe broadcasting officers can work more efficiently and effectively. The tool used to describe the general system design that will be built is UML (Unified Modeling Language) with employees, broadcasters and also management as the main actors in this system, so that a design is formed with the first step, namely someone adding or filling in broadcast data that has been arranged in such a way, then the data is stored and can be changed at any time if necessary. Data can also be printed automatically in excel or PDF format. With this, broadcasters or officers who are responsible for schedulingbroadcasts every day no longer need to use Microsoft Word as a tool. This information system is expected to help and relieve those in need and can be developed further over time.